The Effect of Financial Performance and Corporate Governance on Sustainability Report Disclosure with Company Size as a Moderation - Difa Putra Purnama; Bestari Dwi Handayani (Accounting and Finance Studies, 2021)
The purpose of this study is to test and analyze the influence of profitability, liquidity, leverage, board of directors, independent commissioners, and audit committees on the disclosure of sustainability reports with the size of the company as moderating variables.The population in this study is state-owned companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019.Purposive sampling technique is used as a sample selection technique and obtained samples as many as 14 companies with 56 analytical units.The analysis techniques applied are descriptive analysis and classical assumption test as well as moderation regression analysis model using interaction test.The results of the study showed that the company's activity variables had a positive and significant effect on the disclosure of sustainability report.Independent commissioners negatively and significantly influence the disclosure of sustainability reports.While profitability, liquidity, leverage, board of directors, and audit committee have no effect on the disclosure of sustainability report.The size of the company moderates and strengthens the influence of independent commissioners on the disclosure of sustainability reports.The size of the company moderates and weakens the influence of the company's activities on the disclosure of sustainability reports.The company's size cannot moderate the impact of profitability, liquidity, leverage, board of directors, and audit committees on sustainability report disclosures.